2013
DOI: 10.1002/ar.22718
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Patterns of Morphological Variation in the Ectocranial Human Vault

Abstract: The skull is considered a modular structure in which different parts are influenced by different factors and, as a result, achieve adult shape at different ages. Previous studies have suggested that the basicranium presents a modular pattern that distinguishes sagittal and lateral parts, probably affected by the brain and masticatory structures, respectively. The vault of modern humans, in contrast, has been considered as a highly integrated system mainly influenced by brain growth. Here, we explored developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Some authors define an arbitrary threshold for each specimen which allows an apparently better visualization of bone tissue (Bastir & Rosas, ; Delye et al, ; Park, Yu, Kim, Lee, & Baik, ; Heuzé et al, ; Kim et al, ; Stull et al, ; Titiz, Laubinger, Keller, Hertrich, & Hirschfelder, ). Others define one standard threshold for all specimens which can then be manually adjusted to better visualize the anatomy of a particular individual (Anzelmo, Barbeito‐Andres, Ventrice, Pucciarelli, & Sardi, ; Barbeito‐Andrés et al, 2012; Barbeito‐Andres, Anzelmo, Ventrice, Pucciarelli, & Sardi, ; Cavalcanti et al, ; Chen, Por, Liou, & Chang, ; Decker, ; Hassan et al, ; Hwang et al, ; Kragskov et al, ; Morimoto, Ogihara, Katayama, & Shiota, ; Van Cauter et al, ; Young et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors define an arbitrary threshold for each specimen which allows an apparently better visualization of bone tissue (Bastir & Rosas, ; Delye et al, ; Park, Yu, Kim, Lee, & Baik, ; Heuzé et al, ; Kim et al, ; Stull et al, ; Titiz, Laubinger, Keller, Hertrich, & Hirschfelder, ). Others define one standard threshold for all specimens which can then be manually adjusted to better visualize the anatomy of a particular individual (Anzelmo, Barbeito‐Andres, Ventrice, Pucciarelli, & Sardi, ; Barbeito‐Andrés et al, 2012; Barbeito‐Andres, Anzelmo, Ventrice, Pucciarelli, & Sardi, ; Cavalcanti et al, ; Chen, Por, Liou, & Chang, ; Decker, ; Hassan et al, ; Hwang et al, ; Kragskov et al, ; Morimoto, Ogihara, Katayama, & Shiota, ; Van Cauter et al, ; Young et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…3 and 4). Some studies described similar trends of morphological changes considering the sagittal profile (Bookstein et al, 2003;Anzelmo et al, 2013) while in the present work, lateral variation in the vault and the base was also evaluated. Here, it was shown that infant globular vaults are characterized not only by shorter and higher configurations but also by marked laterally expanded frontoparietal regions (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…En HSAM estos músculos son relativamente débiles, lo que se evidencia en la ausencia de superestructuras óseas prominentes para la inserción muscular, tal como se observa en otros primates (Moss y Young, 1960;Aiello y Dean, 2002). Por esto, se acepta que el encéfalo es el principal modelador de la forma y el tamaño del neurocráneo y más particularmente del endocráneo (Moss y Young, 1960;Anzelmo et al, 2013). La base se ve adicionalmente afectada por los cambios que ocurren en la región facial y la columna vertebral (Lieberman, et al, 2000a, b).…”
Section: Un Marco Para El Estudio Del Crecimiento Y Desarrollo Craneounclassified
“…Tanto en la bóveda como en la base, el modelo que separa los rasgos laterales de los mediales no encontró sustento suficiente en los resultados. Esto coincide con lo descripto por Anzelmo et al (2013) quienes hallaron que los rasgos sagitales y laterales de la bóveda completan su maduración coordinadamente, lo cual es una evidencia de integración entre ambas. La discrepancia con otros estudios en los que se sostienen estos módulos (Bastir y Rosas, 2005) podría ser atribuida a las diferencias respecto de los puntos morfométricos relevados, además de que Bastir y Rosas (2005 relevaron puntos en radiografías laterales, un soporte diferente al empleado en esta tesis.…”
Section: Modelos De Modularidad Dentro Del Neurocráneounclassified